The State of Things: The Dynamic Efficiency of Australian State and Territories. Issue 3 (1st July 2015) - Drew, Joseph; Dollery, Brian
<x xml:space="preserve">Abstract</x> This paper uses intertemporal and locally intertemporal data envelopment analysis to examine inter alia how yardstick competition, heterogeneity, innovation and competition for business and capital manifest themselves in the Australian federation over the period 2007–2012. The incidence of the Global Financial Crisis during this period also facilitated the testing of a hypothesis on how Australian state and territory jurisdictions might be expected to respond to a uniform macro‐economic shock. Intertemporal evidence provided support for the contention that federalism fosters "democratic laboratories." The locally intertemporal analysis provided empirical evidence to support the hypothesis that competitive tensions result in increases to the relative efficiency ceteris paribus of sub‐optimal jurisdictions over time. Moreover, some evidence was found to support the proposition that imitation of best practice leads to converging efficiency between comparable peer jurisdictions.